2020
DOI: 10.1002/batt.202000226
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Induced Kinetics Enhancement in Layered P2‐Na0.67Ni0.33Mn0.67O2 Porous Microcuboids Enables High Energy/Power Sodium‐Ion Full Battery

Abstract: P2‐type Na0.67Ni0.33Mn0.67O2 cathode material generally suffers from poor cycling and rate performance due to fiercely phase variation and low Na+ diffusion kinetic. Although efforts have been made to promote the electrochemical properties through ionic doping, the specific capacity reduction in most cases since the doped cations are electrochemical inactive cannot be neglected. Recently, some pioneering work have demonstrated that the advanced morphological design could significantly improve Na+ intercalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Impressively, compared with the electrochemical properties tested under the mass loading of 2 mg cm −2 , the sodium‐ion full cells with mass loading of 4 and 6 mg cm −2 only show a slightly decreased specific capacity (<4 mAh g −1 ) while the cycling performances are well maintained, which indicates the possibility of its practical application under high mass loading conditions. Compared with recently reported full cell devices based on P2‐Na 0.67 Ni 0.33 Mn 0.67 O 2 layered oxides and other type cathodes, [ 11,22,27,36,52–63 ] as shown in Tables S5 and S6 (Supporting Information), the electrochemical properties of NZNCMO//hard carbon exhibit a balanced advantage considering the simultaneous requirement on the energy density and cycling life, suggesting the great potential of practical applications.…”
Section: Resultsmentioning
confidence: 88%
“…Impressively, compared with the electrochemical properties tested under the mass loading of 2 mg cm −2 , the sodium‐ion full cells with mass loading of 4 and 6 mg cm −2 only show a slightly decreased specific capacity (<4 mAh g −1 ) while the cycling performances are well maintained, which indicates the possibility of its practical application under high mass loading conditions. Compared with recently reported full cell devices based on P2‐Na 0.67 Ni 0.33 Mn 0.67 O 2 layered oxides and other type cathodes, [ 11,22,27,36,52–63 ] as shown in Tables S5 and S6 (Supporting Information), the electrochemical properties of NZNCMO//hard carbon exhibit a balanced advantage considering the simultaneous requirement on the energy density and cycling life, suggesting the great potential of practical applications.…”
Section: Resultsmentioning
confidence: 88%
“…The effects of dopants on the suppression of P2-O2 phase transformation are further investigated by evaluating the stacking fault energies for Na 23 prefer to occupy an intermediate "Z" intergrowth structure rather than a pure O2 structure instead. It is worth mentioning that the similar calculations are also performed by employing the more elaborate optB86b-vdw+U method where both the van der Waals interactions and on-site strong electron correlation effects (U: Ti (3.2 eV), Mn (3.9 eV), and Ni (6.2 eV)) are included in the methodology.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22] Although lowering the charge cut-off voltage (below 4.2 V) offers an effective solution, it comes at the cost of a significant decrease in reversible capacity (< 90 mAh g −1 ) and operating voltage (< 3.2 V). [23][24] By contrast, ion substitution/doping strategy shows greater flexibility in balancing cyclic stability and capacity. It has been demonstrated that Li + , Mg 2+ , Cu 2+ , Zn 2+ , Ti 4+ ions can effectively inhibit the P2-O2 phase transition in P2-Na 2/3 Ni 1/3 Mn 2/3 O 2 and improve its cycling performance.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained large capacity and high voltage of the full cell at high rates ensure that an energy density of ≈165 Wh kg −1 can be maintained even at 10 C in Figure 7f (corresponding to state‐of‐the‐art power density of ≈1650 W kg −1 ). The energy density and power density of this P2‐NaNCMO//hard carbon are compared with those previously reported in literatures, [ 55–64 ] as shown in Figure 7g and Table S2, Supporting Information. This P2‐NaNCMO//hard carbon full cell shows a higher energy density and a higher power density.…”
Section: Resultsmentioning
confidence: 76%